Analisis Konstruksi Sosial dalam Kegiatan Karnaval pada Masyarakat Muncar Banyuwangi - Anis Kumalasari; Faiza Faridatun Ni’mah; Lisa Nur Riski Wulandari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Carnival is the right place to express people's creativity in expressing and showing their local culture, the people of Muncar hold a carnival festival not only to commemorate Independence Day but also to commemorate Suroan, carnival has become a tradition during Suroan, this is also a form of preserving traditional culture and introducing traditional culture to the younger generation. Carnival itself in social construction theory is seen as an event where people actively create and maintain their collective identity. This research highlights the participation of the local Muncar community in showing the symbols of their traditions as outlined in carnival activities and how this carnival is used as a form of suroan tradition. In this research, qualitative research methods are used which will explain the phenomenon descriptively, data obtained through observation and supported by previous research literature study.